2018
DOI: 10.1103/physreva.97.013614
|View full text |Cite
|
Sign up to set email alerts
|

Quasi-one-dimensional spin-orbit- and Rabi-coupled bright dipolar Bose-Einstein-condensate solitons

Abstract: We study the formation of stable bright solitons in quasi-one-dimensional (quasi-1D) spin-orbit-(SO-) and Rabi-coupled two pseudospinor dipolar Bose-Einstein-condensates (BECs) of 164 Dy atoms in the presence of repulsive contact interactions. As a result of the combined attraction-repulsion effect of both interactions and the addition of SO and Rabi couplings, two kinds of ground states in the form of self-trapped bright solitons can be formed, a plane-wave soliton (PWS) and a stripe soliton (SS). These quasi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(5 citation statements)
references
References 81 publications
0
5
0
Order By: Relevance
“…where δ = (1 − B/ Ã)/(1 + B/ Ã), Ã = gn + 2ω R , and B = 4ω R (gn + ω R ). The mean-field contribution of Rabi coupling gives rise to an energy per particle shift [47,48]. However, we show that for fixed values of energy cutoff ǫc = 10, and the coupling constant g = 0.6, the increase of ω R in the quantum correction induces a self-bound droplet instability as plotted in Fig.…”
mentioning
confidence: 70%
“…where δ = (1 − B/ Ã)/(1 + B/ Ã), Ã = gn + 2ω R , and B = 4ω R (gn + ω R ). The mean-field contribution of Rabi coupling gives rise to an energy per particle shift [47,48]. However, we show that for fixed values of energy cutoff ǫc = 10, and the coupling constant g = 0.6, the increase of ω R in the quantum correction induces a self-bound droplet instability as plotted in Fig.…”
mentioning
confidence: 70%
“…Tononi et al in SO coupled BECs demonstrated that the self-bound states are solitonic for vanishingly small MF contribution [27]. Depending upon the Rabi and SO coupling parameters range, these soliton-like states are either of single peak (bright soliton) or multiple peaks (stripe soliton) nature [27,28,31,32].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, the experimental realization of artificial SOC has revolutionized the quantum manipulation of ultracold atoms [12]. This novel system has incorporated various elements, such as artificial magnetic fields, optical lattices [13][14][15][16][17], and dipole interactions [18][19][20], introducing a plethora of physical phenomena in BEC. Examples include the emergence of plane-wave (PW) phases [21,22], stripe phases [18,[23][24][25][26][27][28], vortices [29][30][31][32], lattice phases [27,33], topological superfluid phases [34,35] and supersolid phases [36,37].…”
Section: Introductionmentioning
confidence: 99%